2016
DOI: 10.1007/s10021-015-9951-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Catchment Manipulations of Internal and External Loading Reveal the Sensitivity of a Century-Old Reservoir to Hypoxia

Abstract: Climate change is predicted to have widespread impacts on freshwater lake and reservoir nutrient budgets by altering both hypolimnetic hypoxia and runoff, which will in turn alter the magnitude of internal and external nutrient loads. To examine the effects of these potential climate scenarios on nitrogen (N) and phosphorus (P) budgets, we conducted a whole-catchment manipulation of hypolimnetic oxygen conditions and external loads to Falling Creek Reservoir (FCR), an old, eutrophic reservoir in a reforested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 47 publications
2
64
0
Order By: Relevance
“…The best fitting model for T1 ebullition exhibited positive associations with temperature and mean wind speed and a negative association with ∆ pressure . Using FCR's longitudinal gradient as a guide, T1 is upstream of the primary inflow to FCR and below a wetland (Gerling et al, ), which likely had a strong influence on the CH 4 ebullition dynamics at this site. Wetlands are known to emit large quantities of CH 4 via ebullition (reviewed in Whalen, ), and previous studies have found that the same physical variables in the best fitting model for T1 also drive ebullition rates in wetlands (Aben et al, ; Goodrich et al, 2011; Morin et al, ; Whalen, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The best fitting model for T1 ebullition exhibited positive associations with temperature and mean wind speed and a negative association with ∆ pressure . Using FCR's longitudinal gradient as a guide, T1 is upstream of the primary inflow to FCR and below a wetland (Gerling et al, ), which likely had a strong influence on the CH 4 ebullition dynamics at this site. Wetlands are known to emit large quantities of CH 4 via ebullition (reviewed in Whalen, ), and previous studies have found that the same physical variables in the best fitting model for T1 also drive ebullition rates in wetlands (Aben et al, ; Goodrich et al, 2011; Morin et al, ; Whalen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, wind speed was not a significant predictor of CH 4 diffusion at any transect or at the whole‐reservoir scale, in contrast to earlier studies (Berg et al, 2017; Cole et al, ; Wanninkhof, ). However, FCR is a small, sheltered reservoir in a steep forested watershed that is protected from higher winds (Gerling et al, ). A similar spatiotemporal CH 4 emission study in naturally formed lakes also found that wind speed was not a significant predictor of CH 4 diffusion in two of the three lakes at the Skogaryd Research Catchment, Sweden (Natchimuthu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of minute‐resolution oxygen sensors, an experimental hypolimnetic oxygenation system, and the ability to manipulate external loading from the upstream reservoir, Gerling showed that the reservoir was a net sink of N and P and thus provides an important ecosystem service in reducing nutrient loads to downstream ecosystems (Gerling et al. ).…”
mentioning
confidence: 99%
“…Paralleling Williamson ' s talk, Alexandra Gerling (Virginia Tech) evaluated the importance of external nutrient loading vs. within-lake nutrient recycling-this time by chemical mechanisms rather than biological-for N and P budgets in Falling Creek Reservoir, Virginia (USA). Taking advantage of minute-resolution oxygen sensors, an experimental hypolimnetic oxygenation system, and the ability to manipulate external loading from the upstream reservoir, Gerling showed that the reservoir was a net sink of N and P and thus provides an important ecosystem service in reducing nutrient loads to downstream ecosystems (Gerling et al 2016 ).…”
mentioning
confidence: 99%